Pengaruh Beban Pajak, Non Debt Tax Shield, Profitabilitas, Kepemilikan Manajerial Terhadap Struktur Modal - linda; Nana Umdiana; Denny Putri Hapsari ("LAWSUIT" Jurnal Perpajakan, 2023)
This study aims to determine whether there is an effect of Tax Burden, Non Debt Tax Shield, Profitability and Managerial Ownership on Capital Structure. This research was conducted on Basic Industry and Chemical Subsector Companies listed on the Indonesia Stock Exchange 2016-2020. Obtained a sample of 13 companies using purposive sampling method. Research data is secondary data, namely financial statements that have been audited and obtained through the official website of the Indonesia Stock Exchange. This study uses multiple linear regression analysis using the partial test hypothesis (T) and uses the classical assumption test consisting of normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test. The results of this study indicate that partially the tax burden has no effect on capital structure, non-debt tax shield has no effect, profitability has no effect on capital structure, managerial ownership has no effect on capital structure. And simultaneously has a significant effect on the capital structure. Keywords: tax burden, non debt tax shield, profitability, managerial ownership, capital structure